Variable-order fuzzy fractional PID controllers for networked control systems - Dingyu Xue; Lu Liu; Feng Pan (2015 IEEE 10th Conference on Industrial Electronics and Applications (ICIEA), 2015)
A variable-order fuzzy fractional PID controller which combined fractional calculus and fuzzy control algorithm together is proposed in the paper. Compared with other fuzzy controllers, the proposed fuzzy inference system had two inputs and five outputs, so that all the five parameters of the fractional-order PID controller are tuned, subject to the changes in the plant, and usually better control performance can be achieved. The controller presented is demonstrated to be effective when there exist fixed or stochastic transport delays in networked control systems. Simulations analysis of the presented variable-order fractional fuzzy PID controller and another two controllers applied on two representative networked plants with or without transport delays are carried out to show the benefit of the proposed controller.